The Dynamics of Vertical Coordination in Agrifood Chains in Eastern Europe and Central Asia : Implications for Policy and World Bank Operations - World Bank (Washington, DC, 2012)
A major problem in the transition countries of Europe and Central Asia (ECA) during the transition was the breakdown of the relationships of farms with input suppliers and output markets. The simultaneous privatization and restructuring of the farms and of the up- and downstream companies in the agrifood chain has caused major disruptions. The result is that many farms and rural households face serious constraints in accessing essential inputs (feed, fertilizer, seeds, capital, etc.) and in selling their products. The problems are worsened by the lack of public institutions necessary to support market-based transactions, such as for enforcing property rights and contractual agreements. In the absence of appropriate public institutions, private contractual initiatives, often from large food and agribusiness companies, are emerging to overcome these obstacles. Large traders, agribusinesses, and food processing companies, often as part of their own restructuring or following foreign investment, start contracting with the farms and rural households and provide basic inputs in return for guaranteed and quality supplies. This process of interlinked contracting, called vertical coordination, is growing rapidly in ECA agriculture and rural areas. This report pinpoints unresolved issues related to efficiency, equity, and government policy. As a part of its analysis, the report identifies options for improved policies, institutions, and investments which Governments could make, and which the World Bank could support, in order to improve links in agricultural marketing and processing chains and increase access of farmers to input and output markets.